Analisis Faktor-Faktor Yang Mempengaruhi Minat Masyarakat Terhadap Produk Keuangan Syari’ah - Syamsuddin; Ngatmin Abbas; Mutia Azizah Nuriana (Universitas Ahmad Dahlan, 2024)
This study aims to analyze the factors influencing public interest in Sharia-compliant financial products in Indonesia. The primary focus is to understand how public understanding and education impact their interest in products such as savings, deposits, insurance, pawnshops, and Sharia-compliant securities. This research employs a qualitative approach using a literature review method. Data were collected from various relevant literature sources, including journals, books, reports, and scientific articles. Descriptive analysis was conducted to identify key patterns and themes related to the factors influencing public interest in Sharia-compliant financial products. The results indicate that the level of public understanding and education significantly affects their interest in Sharia-compliant financial products. People with a better understanding of Sharia principles and the mechanisms of Sharia-compliant financial products tend to be more interested and confident in using these products. Sharia financial literacy programs, integration of Sharia finance materials into educational curricula, and practical training and workshops have proven effective in increasing public understanding and interest. Therefore, improving public education and understanding is expected to drive the growth of the Sharia finance industry in Indonesia.